The impact of an integrated value chain intervention on household poultry production in Burkina Faso: Evidence from a randomized controlled trial - Leight, Jessica; Awonon, Josué; Pedehombga, Abdoulaye; Ganaba, Rasmané; Martinez, Elena M.; Heckert, Jessica; Gelli, Aulo (Informa UK Limited, 2022)
This article reports on a cluster-randomised controlled trial conducted in rural Burkina Faso evaluating a multifaceted intervention, SELEVER, that seeks to increase poultry production by delivering training and strengthening of village-level institutions providing veterinary and credit services. Households exposed to the intervention significantly increase their use of poultry inputs (veterinary services, enhanced feeds, and deworming), and report more poultry sold and higher revenue. However, there is no evidence of an increase in profits. This evidence is consistent with the hypothesis that the return to inputs may not be sufficient to counterbalance the market costs of these inputs.